Pharmacotherapeutics role of Cannabinoid (CB1 & CB2) Receptor agonists modulator in chemotherapy-induced peripheral neuropathy: A Review - Bhatt, Amit Kumar; Kumar Sharma, Krishana (Journal of Neonatal Surgery, 2025)
The injury or illness of the somatosensory nerve system results in pain termed neuropathic pain. It often increases dependence on medication as well as the need to visit hospitals. Allodynia, hyperalgesia, and paresthesia are symptoms that are produced by this disorder. In animal studies, “Chronic constriction injury (CCI), partial sciatic nerve ligation (Seltzer model), and spinal nerve ligation (SNL) are methods used to reproduce it. Chemotherapy induced peripheral neuropathy (CIPN) is the most common kind of neuropathic pain among the wide range of manifestations.It frequently results from the use of chemotherapeutic agents, which include but are not limited to ixabepilone, thalidomide, taxanes, and platinum compounds.” While opioids are commonly prescribed for CIPN, these drugs cannot be safely used for prolonged periods due to the high potential for addiction. There has been increasing attention given to cannabinoid receptors, particularly CB2, because of their role in the modulation of inflammation and pain. This review analyzes the possible therapeutic effects of CB2-selective agonists on CIPN and other neuropathic disorders. More recently, itaconates and isatins have been discovered to be CB2 agonists and they show promise in preclinical studies. This article focuses on the neuropathic pain mechanisms associated with these agents’ analgesic effects..